Análisis del comportamiento de la exportación de aceites crudos de petróleo a partir de la firma del acuerdo de la alianza del pacífico (2017)
In Colombia, oil has become the engine of the economy and the fundamental basis of the state's finances. The high dependence that has been generated from oil, despite the changes in its regulations, the findings of producing fields has not been sufficient when faced with the instability that characterizes the international market and the fluctuations in the prices of this product. as it has been seen that the country's economy has been unstable. Given the importance that oil has had in the export profile of the Colombian economy and the achievement that has been obtained with the consolidation of the Pacific Alliance (AP), which seeks to further increase the incursion of member countries to international markets , I wanted to investigate how this consolidation has influenced the behavior of exports of crude oil oils to Colombia, since in moments of crisis in this vitally important sector, it is necessary to take full advantage of the agreements that are with the international community.